The Effect Of Financing To Deposit Ratio (FDR), Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), Operating Expenses And Operating Income (BOPO) On ROA In Islamic Commercial Ban - Anni Aisyah Hasibuan; Zulpahmi Zulpahmi; Nur Wahyudin; Azza Nurlaila (AL-FALAH : Journal of Islamic Economics, 2022)
Purpose: The purpose of this research is to analyze the influence of Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), Operating Expenses and Operating Income (BOPO) on Return On Assets (ROA) during the period of 2015-2021 Syariah banks in Indonesia.Design/Method/Approach : . This research is a quantitative study on the population of Islamic Commercial Banks in Indonesia registered with the Financial Services Authority (OJK). The data used for this research were obtained from the data of the Annual Published Financial Report Period 2015 up to 2021. The analysis technique used Partial Least Squares (PLS) which are used to test the inner model and outer model.Findings: The results of this study indicate that partially the FDR variable has a significant negative effect on ROA, and NPF has a significant negative effect on ROA. In comparison, CAR and BOPO have a positive and significant effect on ROA. The predictive ability of these variables on Profitability (ROA) in this study was 46,2% and while the remaining 53,8% was influenced by other factors not included in the study.Originality/Values: It can be concluded that the financing to deposit ratio (FDR), capital adequacy ratio (CAR), non-performing financing (NPF), and Operating Expenses to Operating Income (BOPO) altogether influence the return on assets (ROA). In Islamic Commercial Bank in Indonesia the period 2015 to 2021, non-performing financing (FDR) has a negative effect on ROA, and non-performing financing (NPF) has a negative effect that influences the ROA of Islamic Commercial Bank in Indonesia in the period 2015-2021. Capital adequacy ratio (CAR) has a positive effect on the ROA of Islamic Commercial Bank in Indonesia from 2015 to 2021, and Operating Expenses to Operating Income (BOPO) has a positive effect on the ROA of Islamic Commercial Bank in Indonesia from 2015 to 2021. Banking companies are expected to penalize the financial ratios that can be a reference bank to be able to identify problems and conduct appropriate follow-up improvements. If there is an increase in the NPF, it indicates the ineffectiveness of the loan issued by the bank.